First records of Trichocircus Jałoszyński and Protandroconnus Franz in Mexico, with descriptions of two new species (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Trichocircus and Protandroconnus are Neotropical genera of Glandulariini characterized, among other features, by unusual male cephalic modifications. The recently described Trichocircus comprises three species distributed in Panama and Costa Rica, and Protandroconnus includes one species, known to occur in Peru. Both genera are recorded as new for Mexico, and two new species are described: Trichocircus mexicanus sp. n., and Protandroconnus akeratophorus sp.n. The latter is unusual in lacking the frontal ‘horn’ known for the type species of Protandroconnus; instead the head of male bears a peculiar transverse impression.